Online learning videos to develop creative thinking skills of students - Mila Ermilia Hendriyani; Ika Rifqiawati; Diana Lestari (Universitas Muhammadiyah Malang, 2022)
Creative thinking skills are 21st Century Skills which are difficult to improve when online learning is implemented. This study aimed to develop online learning videos to improve students' creative thinking skills. The product development process includes problem analysis, material collection, product design, expert test, limited trial, design revision, usage trial, and product revision. The material and design determine the feasibility of the product. Aspects of material assessment include conformity to the curriculum, indicators of creative thinking, and language. Elements of the assessment in terms of media include instructional design, visual communication, and aspects of creative thinking. The validation results show the average percentage of material experts is 97.55%, and media experts is 93.7%. The results of the user response test (teachers and students) were 99.76%. This value shows that online learning videos were included in the very appropriate category as learning media to improve students' creative thinking skills on the material of the circulatory system. Therefore, the media that has been developed in this study is expected to be followed up in further research and applied in biology learning.